81 INTRAUTERINE GROWTH RESTRICTION ALTERS HISTONE CODE ALONG THE RAT HEPATIC INSULIN-LIKE GROWTH FACTOR 1 LOCUS. Issue 1 (1st January 2007) - Fu, Q.; McKnight, R. A.; Yu, X.; Men, P.; Lane, R. H.
Abstract : Objective: Intrauterine growth restriction (IUGR) alters insulin-like growth factor 1 (IGF-1) levels in humans. IGF-1 messenger ribonucleic acid levels in day 0 IUGR rat liver are reduced to 25% in males and 40% in females compared with controls. In humans and rats, IGF-1 expression involves epigenetic regulation, including the use of different promoters, alternative exon splicing, and transcription termination. Epigenetic regulation of gene expression is mediated in part by changes to chromatin structure due to post-translational modifications of histones (histone code). We hypothesized that the histone code associated with the IGF-1 gene is vulnerable to uteroplacental insufficiency and subsequent IUGR, leading to alterations in IGF-1 expression. Methods: IUGR rats were generated by bilateral uterine artery ligation of pregnant e19 dams. Cesarean section was performed at term (day 0) and liver was harvested. Chromatin immunoprecipitation (ChIP) was performed with acetyl-K9/H3, acetyl-K14/H3, me 2 -K4/H3, me 3 -K4/H3, me 3 -K9/H3, and me 3 -K36/H3 antibodies at a resolution of 500 to 2, 000 bp on control and IUGR day 0 rat livers. Real-time polymerase chain reaction was used to quantify promoters P1 and P2, exon 5, proximal 3′ UTR, and distal 3′ UTR. An intergenic sequence 230 kb 3′ of IGF-1 gene was used as internal control. Results: Along the IGF-1 gene, acetyl-K9/H3, me 2 -K4/H3, and me 3 -K4/H3 were greatest at the P2 region, whereas me 3 -K36/H3 accumulated within the body and toward the downstream region of the gene. Me 3 -K9/H3 distributed evenly along the IGF-1 gene. IUGR significantly increased acetyl-K14/H3 along the entire IGF-1 locus in female day 0 rat liver, whereas acetyl-K9/H3 was not affected in either males or females. IUGR significantly increased me 2 -K4/H3 at P1, P2, and exon 5 in the male day 0 rat liver but unaltered in females. Me 3 -K4/H3 was significantly increased at P1 in female day 0 IUGR rat liver, whereas there was no change in males. Me 3 - K9/H3 was not influenced by IUGR in both genders. IUGR significantly decreased me 3 - K36/H3 at all the five sites in females and at P2 in males. Conclusion: The hepatic IGF-1 gene shows unique patterns of histone H3 covalent modifications. Uteroplacental insufficiency and subsequent IUGR alter these patterns across the IGF-1 locus in a gender-specific manner. Speculation: We speculate that gender-specific differences in the IGF-1 histone code may be, in part, responsible for phenotypic differences between male and female IUGR individuals.